Utilizing Video Subtitling in Writing Procedure Text - Halimah Halimah; Mela Zahra; Nia Kurniawati (Universitas Cokroaminoto Palopo, 2021)
This study aims to investigate how the utilization of video subtitling in writing procedure text, what are difficulties the teacher and students encountered, and the benefits the students gained by implementing video subtitling in writing procedure text. This study is a descriptive qualitative study. To collect and analyze the data, the researcher used observation, interview, and questionnaire. This study was conducted in SMK Bhineka Nusantara Cianjur. The participants were an English teacher and ten students of tenth grade. The data from those instruments were transcribed and categorized accordingly. The findings show that the teacher applied several main steps in using video subtitling activity: introducing the application namely TikTok, explaining the purpose of TikTok application in teaching and writing procedure text, showing the simulation in translating the sentences and making subtitle with the application, downloading and installing the application, downloading the tutorial video, making the subtitle and inserting the subtitle to the video. The application helps the teacher in assisting remote classroom activity and delivered the material under the pandemic situation. In this case the students were enthusiastic when the teacher implemented the application and they felt familiar with it. However, the teacher and the students encountered some difficulties in writing procedure text using video subtitling: ineffective learning process monitoring by the teacher, internet connection problem, and difficult editing process. Albeit there were some difficulties, the students also gained number of benefits of using video subtitling in writing procedure text: more interesting learning activity, producing organized text and stimulating creativity, and vocabulary acquisition.